MAKELAR KASUS (MARKUS) DALAM PERSPEKTIF HUKUM ISLAM (SEBUAH UPAYA PENCEGAHAN MAKELAR KASUS) - Chanifah, Nur (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2011)
Cases middleman is one of corruption types. In islamic law it is recognized asÂ ârisywahâ, in which according to the law is forbidden to be conducted (haram). The law also has been stated in Qurâan and Hadist. One of the media in conducting this forbidden practice is using the service of cases middleman. The existence of cases middleman makes the practice of corruption higher along the time. Meanwhile, it is generally known that in Indonesia, most of the population aremoslem. Moslem should be able to obey the rule of Islam. Therefore, Islam must give huge contributions to prevent the act of cases middleman, in order to reduce and eliminate corruption. The preventive action can be in the effort of making good salary system, good leader model, society supervision, strong faith, etc. Key words: Islamic law and cases middleman